Comparative outcomes of surgical fixation versus conservative management in clavicle fractures: A prospective cohort study. - Padamwar , Anup Kumar; Jain, Keyur (Student's Journal of Health Research Africa, 2025)
Background This study aimed to compare the clinical outcomes of conservative versus surgical intervention in patients with clavicle fractures. Methods A prospective study was conducted on 50 patients with clavicle fractures, allocated into two groups: 25 patients managed conservatively (arm sling) and 25 undergoing surgical fixation (open reduction and internal fixation with plates). Baseline characteristics, fracture union time, functional outcomes (Constant-Murley Shoulder Score), pain levels (Visual Analog Scale), complications, and return to work/activity time were recorded. Statistical analyses included chi-square tests for categorical variables and t-tests for continuous variables, with p < 0.05 considered significant. Results Baseline demographics were comparable between groups (p > 0.05). The surgical group achieved significantly faster fracture union (9.2 ± 1.5 weeks) compared to the conservative group (13.5 ± 2.1 weeks, p < 0.001). Functional outcomes favored the surgical group (88.6 ± 6.2) over the conservative group (79.3 ± 7.8, p = 0.002). Nonunion and malunion were more frequent in the conservative group (p = 0.04 and p = 0.03, respectively), while superficial wound infections occurred in 8% of surgical cases. Pain scores were significantly lower in the surgical group (1.3 ± 0.9) versus the conservative group (2.8 ± 1.2, p = 0.001). Return to work was earlier in the surgical group (10.5 ± 2.3 weeks) than in the conservative group (15.7 ± 3.1 weeks, p < 0.001). Conclusion Surgical intervention in clavicle fractures provides superior union time, functional outcomes, lower pain scores, and quicker return to activity compared to conservative management, with an acceptable complication profile. Recommendations Surgical fixation should be preferred for displaced midshaft clavicle fractures in active individuals to ensure faster recovery and better function. Conservative treatment remains suitable for minimally displaced fractures or patients with lower functional demands. Larger studies with longer follow-up are encouraged.